Penerapan Diversi Tindak Pidana Anak Dalam Penggunaan Senjata Tajam - Istiqomah, Mila; Sihombing, L Alfies; Rianto, Astim (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2024)
Article 7 paragraph (2) of the SPPA Law limits the implementation of diversion only to criminal acts which are punishable by a sentence of less than seven years, so that criminal acts which are punishable by more than seven years cannot be attempted. This article discusses the application of diversion at the investigation, prosecution and evidentiary stages and the judge's considerations in Decision Number: 15/pid.sus.anak/2021/PN.BGR in the case of possession of sharp weapons. The author uses normative juridical research methods. The results of this research conclude that diversion must be carried out during the investigation, prosecution and evidence stages in court. The judge was of the opinion that in this case diversion could not be applied considering that the child was charged under Article 2 paragraph 1 of the Emergency Law of the Republic of Indonesia no. 12 of 1951 with a penalty of 10 years in prison, so that child offenders cannot be diverted. The conditions for diversion limit implementation, so that if the perpetrator and victim agree to reconcile, diversion cannot still be carried out. Therefore, it is necessary to have provisions that can give authority to Law Enforcement Officials to carry out diversion based on an objective assessment and agreement between the parties, even though this case is punishable by a sentence of more than 7 years in prison.